Deciphering the signature of seedborne fungi linked to rice sheath rot disease: insights from ITS rDNA sequencing analysis - Hoerussalam, Hoerussalam; Afifuddin, Ahmad; Lathif, Yudrik; Widiastuti, Ani; Putra, Eka Tarwaca Susila; Priyatmojo, Achmadi (Universitas Lampung, 2026)
Sarocladium oryzae and Fusarium spp. are the causal agents of sheath rot, a re-emerging rice disease that has recently gained importance in Indonesia and can cause yield losses of up to 85%. Both pathogens are seedborne, making their accurate identification and management essential. Conventional morphological identification is time-consuming and often inaccurate due to overlapping symptoms among fungal species. In this study, we demonstrated the seedborne transmission of sheath rot pathogens and provided novel insights by highlighting the predominance of F. equiseti and the detection of infections in asymptomatic seeds. A total of 75 fungal isolates were obtained from rice leaf sheaths, seeds, and harvested grains across CMS, inbred, and hybrid rice varieties. ITS rDNA sequencing identified 42 isolates as S. oryzae and 33 as Fusarium spp., including F. equiseti (29), F. incarnatum (1), and F. proliferatum (3). The detection of these pathogens in both pre-planting seed samples and post-harvest grains demonstrates their ability to spread through seeds. Importantly, their presence in asymptomatic seeds and grains indicates that routine visual inspection is insufficient for seed health monitoring.